The Role of the United Nations High Commissioner for Refugees (UNHCR) In the Protection of Afghan Refugees in Indonesia amid the Covid-19 Pandemic - Siti Nadhifah Eprillia Salsabila (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
One of the refugees that became the focus of this study is Afghan refugees in Indonesia in the middle of the COVID-19 pandemic. The purpose of this study is to understand the role of the United Nations High Commissioner for Refugees (UNHCR) in protecting Afghan refugees in Indonesia amidst the COVID-19 pandemic. This research used descriptive research that looks at reality by compiling conceptual research. The limit period of this study is 2019-2021 because it is the year the COVID-19 pandemic occurred. The results showed that UNHCR's role for Afghan refugees in Indonesia during the Covid-19 pandemic was to provide assistance to refugees in Indonesia, amounting to Rp. 6 million UNHCR continues to advocate for refugees to access their fundamental rights, including their access to health, education, empowerment, and livelihoods. Besides that, UNHCR has also assisted refugee rights to cover the cost of basic needs. To overcome the COVID-19 pandemic, the Indonesian government also provided vaccines for free to all refugees, including all migrants from Afghanistan, which are very large in number. The Indonesian government continues to pay attention to how Afghan refugees are handled, especially during disasters, while higher values on the traditional international standards in dealing with refugees, such as non- refoulement.